Post-Training Assistance and Evaluation of Water Safety for the Deaf in DKI Jakarta: Indonesia - Abdul Sukur; Heru Miftahudin; Fajar Vidya Hartono; Masnur Ali; Qory Jumrotul Aqobah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This community service program aimed to provide post-training mentoring and evaluation water safety skills for individuals with hearing disabilities in DKI Jakarta. The program was initiated in response to the limited access to inclusive water safety education and the high risk of water-related accidents among persons with disabilities. The activities focused on strengthening participants’ understanding, practical skills, and independence in applying water safety principles after completing the initial basic training. The implementation methods included direct assistance in swimming pool sessions, the use of visual media and sign language, emergency situation simulations, and structured skill assessments through observation instruments. The evaluation process measured improvements in knowledge, basic water safety techniques, and participants’ responses to potential risk situations in aquatic environments. In addition, reflective discussions were conducted with instructors and facilitators to identify challenges and areas for further program development. The results indicated an increase in participants’ understanding of water safety concepts, improvement in self-rescue skills, and enhanced confidence in engaging in aquatic activities. Continuous mentoring proved effective in strengthening skill retention and minimizing accident risks. This program recommends the development of adaptive, collaborative, and sustainable water safety training models as part of broader efforts to promote inclusive sports and physical education services for individuals with hearing disabilities.